Effect of Pelargonium graveolens essential oil and cyantraniliprole on the feeding behavior of Bemisia tabaci MED - dos Santos, Maria Clezia [UNESP]; Lima, Ana Paula [UNESP]; Farias, Adriano Pimentel [UNESP]; Santana, Alisson Silva; Prado Maluta, Nathalie; Lourenção, André Luiz; Antônio Bernardes, Wagner; Baldin, Edson Luiz Lopes [UNESP]; Lopes, João Roberto Spotti (Wiley, 2024)
The sweet potato whitefly, Bemisia tabaci MED (Gennadius) (Hemiptera: Aleyrodidae), is highly harmful to solanaceous crops. The use of essential oils (EOs) is promising for the management of several insect pests, promoting both lethal and sublethal effects. This study aimed to evaluate the effects of sublethal concentrations of Pelargonium graveolens L'Her (Geraniaceae) EO on the feeding behavior of B. tabaci MED on tomato plants (Solanum lycopersicum L., Solanaceae). For this research, the electrical penetration graph (EPG) technique was used to monitor whitefly stylet activities on their host plants. Two sets of plants were previously sprayed with two concentrations of EO (the LC25 and LC50, which were determined in a mortality test), a third set was treated with the insecticide cyantraniliprole, and a fourth set received a control treatment. Our results indicate that the insecticide cyantraniliprole and the EO could both reduce the stylet feeding activity of B. tabaci MED, as well as reduce the number and duration of phloem sap ingestion events (waveform E2), which could avoid or reduce the transmission of viruses. Thus, the application of sublethal concentrations of P. graveolens EO, as well as exposure to cyantraniliprole, negatively affected the feeding behavior of B. tabaci MED. This information may contribute to the management of this pest and the reduction of the incidence of viruses in tomato production.
Keywords: Aleyrodidae; botanical insecticide; electrical penetration graph; EPG; Geraniaceae; Hemiptera; integrated pest management; IPM; Solanaceae; Solanum lycopersicum; sweet potato whitefly; tomato